The effect of propolis extract and bovine bone graft combination on the number of osteoclast and osteoblast as an effort to preserve post-extraction socket (on Cavia cobaya) - Much Nizar; Utari Kresnoadi; S. Soekobagiono (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: Post-extraction alveolar bone height and width never reach the same dimensions as before extraction. A combination of propolis extracts and bovine bone graft (BBG) that are anti-inflammatory, antioxidant, osteoinductive and osteconductive is expected to improve bone regeneration. Purpose: Knowing the effect of the combination of propolis extracts and BBG on the number of osteoclast and osteoblast as an effort to preserve the socket after extraction of Cavia cobaya teeth. Methods: 56 Cavia cobaya was divided into eight groups: the lower left incisor was extracted, and the socket was filled with 2% poly ethylene glycol (PEG), propolis extract+PEG, BBG+PEG, and a combination of propolis extract+BBG+PEG. The incisors socket of animals models were executed on the 14th and 30th days. Using HE for histopathological examination, the number of osteoclasts and osteoblasts were counted with a 400x magnification light microscope with nine visual fields. The data were analysed via one-way ANOVA and Tukey HSD tests. Results: The highest mean number of osteoclasts occurred in the BBG+PEG 14th day group and the lowest occurred in the propolis extract+BBG+PEG 14th day group. The highest mean number of osteoblasts occurred in the propolis + BBG + PEG combination 30th day group, the lowest occurred in the control group (PEG) on the 14th day. Conclusion: The 2% combination of propolis extracts and BBG effectively reduces the osteoclast number and increases the osteoblast number in preserving the socket after extracting Cavia cobaya teeth.